Strategi Pemasaran Global dalam Menghadapi Krisis Ekonomi dan Geopolitik - Muhammad Farrel Ardyanto; Husein Mizar Pratama; Mohamad Zein Saleh (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
Economic crises and geopolitical tensions have been major factors affecting global market stability and posing major challenges for multinational corporations. This research aims to identify and analyze the global marketing strategies implemented by companies in dealing with these uncertain conditions. Using a descriptive qualitative approach through a literature review, this study found that commonly used strategies include market adaptation, risk diversification, and digital transformation. Market adaptation is carried out through product adjustments, prices, promotions, and distribution to be relevant to local conditions. Risk diversification is implemented by moving supply chains to more stable regions. Meanwhile, digital transformation is used to strengthen interactions with consumers and increase responsiveness to market changes. These findings show that a resilient marketing strategy focuses not only on growth, but also on resilience, flexibility, and sustainable innovation. By understanding the complexity of the global market, companies can design strategies that are able to maintain business competitiveness and sustainability in the midst of a crisis.